2020
DOI: 10.2106/jbjs.19.00554
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Short-Term Patient Outcomes Following Overlapping Orthopaedic Surgery at a Large Academic Medical Center

Abstract: Background: Overlapping surgery is a long-standing practice that has not been well studied. The aim of this study was to assess whether overlapping surgery is associated with untoward outcomes for orthopaedic patients. Methods: Coarsened exact matching was used to assess the impact of overlap on outcomes among elective orthopaedic surgical interventions (n = 18,316) over 2 years (2014 and 2015) at 1 health-care system. Overlap was categorized as any ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…3 Previous literature across multiple surgical services has not demonstrated an increase in morbidity, mortality, or complication rate, despite occasionally finding an increased duration of surgery. [4][5][6][7] There are similar results for overlap within neurosurgery, with previous studies reporting noninferior outcomes following all neurosurgical procedures, 8,9 elective neurosurgical procedures, 10 pituitary adenoma resection, 11 microvascular decompression, 12 and spine surgery. 13 Although these reports suggest that surgical overlap is safe, few studies have evaluated whether an increasing amount of overlap during surgery confers additional risk to patients.…”
Section: Introductionmentioning
confidence: 54%
“…3 Previous literature across multiple surgical services has not demonstrated an increase in morbidity, mortality, or complication rate, despite occasionally finding an increased duration of surgery. [4][5][6][7] There are similar results for overlap within neurosurgery, with previous studies reporting noninferior outcomes following all neurosurgical procedures, 8,9 elective neurosurgical procedures, 10 pituitary adenoma resection, 11 microvascular decompression, 12 and spine surgery. 13 Although these reports suggest that surgical overlap is safe, few studies have evaluated whether an increasing amount of overlap during surgery confers additional risk to patients.…”
Section: Introductionmentioning
confidence: 54%
“…Eleven articles met the inclusion criteria, encompassing a total of approximately 119,410 surgeries (Supplemental Table 2, http://links.lww.com/JAAOS/A958). [1][2][3]5,6,[9][10][11][12][13][14] Of these, 34,494 (29%) were overlapping and 84,916 (71%) were nonoverlapping (Supplemental Table 3, http://links. lww.com/JAAOS/A959).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies consisted of procedures occurring at multiple hospitals, with one study covering procedures at 75 Ontario hospitals. 1,2,6 Variation also existed in the type of orthopaedic procedures occurring (Supplemental Table 2, http://links.lww.com/ JAAOS/A958). The most commonly reviewed surgeries were joint reconstructions, with six of the 11 studies focusing solely on overlapping surgeries in arthroplasty.…”
Section: Resultsmentioning
confidence: 99%
“…The difference of opinion held by surgeons regarding simultaneous surgery compared with their patients may be based on literature showing no clinically significant difference in outcomes between overlapping and non-overlapping surgery. In a study of 18 316 elective orthopaedic procedures (3395 overlapping), Glauser et al 3 found no difference in reoperation, readmission or emergency room visit rates at 30 or 90 days compared with matched controls. In a cohort of 4786 primary THA/TKA patients undergoing simultaneous surgeries of at least 30 minutes, Zachwieja et al 5 found no difference in readmission rate, length of stay or rates of discharge.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have attempted to evaluate outcomes of, as well as patient perspectives regarding, simultaneous surgery. Glauser et al 3 found no short-term adverse outcomes after overlapping surgery at a large academic medical centre. On the other hand, Bryant et al 4 showed that parents of patients undergoing posterior instrumentation and fusion (PSIF) for adolescent idiopathic scoliosis (AIS) were not agreeable to simultaneous scheduling of any type, even when presented with research demonstrating the safety of simultaneous surgery.…”
Section: Introductionmentioning
confidence: 97%